2018
DOI: 10.1021/acschemneuro.8b00107
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s Disease Associated α-Synuclein Familial Mutants Promote Dopaminergic Neuronal Death in Drosophila melanogaster

Abstract: α-Synuclein (α-Syn) aggregation and amyloid formation are associated with loss of dopaminergic neurons in Parkinson's disease (PD). In addition, familial mutations in α-Syn are shown to be one of the definite causes of PD. Here we have extensively studied familial PD associated α-Syn G51D, H50Q, and E46K mutations using Drosophila model system. Our data showed that flies expressing α-Syn familial mutants have a shorter lifespan and exhibit more climbing defects compared to wild-type (WT) flies in an age-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
5
24
1
Order By: Relevance
“…Drosophila models of PD expressing not only WT αSyn but also some familial PD-linked forms of mutant αSyn, such as A30P, E46K, H50Q, G51D, and A53T, have been previously established by random transgenesis [25,33,38]. A30P αSyn-expressing flies were reported to demonstrate stronger phenotypes than WT αSyn-expressing flies, although expression levels of the transgenes were not analyzed [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drosophila models of PD expressing not only WT αSyn but also some familial PD-linked forms of mutant αSyn, such as A30P, E46K, H50Q, G51D, and A53T, have been previously established by random transgenesis [25,33,38]. A30P αSyn-expressing flies were reported to demonstrate stronger phenotypes than WT αSyn-expressing flies, although expression levels of the transgenes were not analyzed [33].…”
Section: Discussionmentioning
confidence: 99%
“…Mohite et al . also established flies expressing each of E46K, H50Q, and G51D by random transgenesis, and analyzed the fly lines with equivalent protein expression levels [38]. Their E46K, H50Q, and G51D αSyn-expressing flies showed more severe declines in locomotor function than WT αSyn-expressing flies.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of the enzymatic antioxidant system is followed by mitochondrial damage via depletion of NPSH and in turn enhances the production of free radicals [54]. Proteotoxicity and the dopaminergic neuronal death in Drosophila due to the expression of alpha synuclein and lewy bodies are well established [55, 56, 57, 58]. We found that PD flies exposed to MB showed decreased TBARS levels which were accompanied by decreased SOD and CAT activity followed by increased NPSH levels.…”
Section: Resultsmentioning
confidence: 78%
“…A30P or G51D flies have a lower climbing ability than normal flies (23,24). Saffron and crocetin significantly suppressed the decrease of climbing ability in the A30P flies ( Fig.…”
Section: Resultsmentioning
confidence: 86%